Soil Sequence at Western Slope of Lawu Volcano - Jamulya, Jamulya (Forum Geografi, 2000)
The objectives of thisÂ  study was sto know the soil sequence according to topographic position on west part of Lawu volcano. Interpretation of topographic map and landsat image, making topographic cross section from upper slope, lower slope to fluvio volcanic plain were carried out for reference the location of soil profile morphological description. Soil morphological description in representative soil profile on every landscape unit. Taking soil samples for analysing physical and chemical properties to know soil development. The result indicatedÂ  that go down to the slope, from upper slope, lower slope to fluvio volcanic plain, there were 4 soil landscape or 4 soil great group i.e. Melamudands (Andosol), Eutrudepts (Latosol), Ferrudalfs (Mediteran), and Udifluvents (Alluvial).